Views of teenagers on termination of pregnancy at Muyexe high school in Mopani District, Limpopo Province, South Africa - Nditsheni J. Ramakuela; Tsakani R. Lebese; Sonto M. Maputle; Lindiwe Mulaudzi (African Journal of Primary Health Care & Family Medicine, 2016)
Background: Teenage pregnancy is a global social health concern especially because of the HIV and AIDS pandemic, sexually transmitted infections, high rate of termination of pregnancy (TOP), adolescents’ parenthood and decreased level of contraceptives.